2013
DOI: 10.1016/j.jat.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal polynomials on the unit circle with Fibonacci Verblunsky coefficients, I. The essential support of the measure

Abstract: Abstract. We consider CMV matrices with Verblunsky coefficients determined in an appropriate way by the Fibonacci sequence and present two applications of the spectral theory of such matrices to problems in mathematical physics. In our first application we estimate the spreading rates of quantum walks on the line with time-independent coins following the Fibonacci sequence. The estimates we obtain are explicit in terms of the parameters of the system. In our second application, we establish a connection betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…On the other hand, a point has a bounded forward orbit if and only if it belongs to a stable manifold of Λ λ (this is known and has been used since Casdagli's work [20]; an explicit proof was given in [39,Corollary 2.5], see also [78]). Since the spectrum is real and the (complexified) line of initial conditions maps R into the real subspace of the invariant surface, all intersection points must be real.…”
Section: Now Let Us Return To Our Case Where σmentioning
confidence: 99%
“…On the other hand, a point has a bounded forward orbit if and only if it belongs to a stable manifold of Λ λ (this is known and has been used since Casdagli's work [20]; an explicit proof was given in [39,Corollary 2.5], see also [78]). Since the spectrum is real and the (complexified) line of initial conditions maps R into the real subspace of the invariant surface, all intersection points must be real.…”
Section: Now Let Us Return To Our Case Where σmentioning
confidence: 99%
“…For some recent contributions on this topic we refer to [5,7,8,10,14,25,27,28,29,34,36] and references there in. Detailed accounts regarding the earlier research on these polynomials can be found, for example, in Szegő [35], Geronimus [18], Freud [17] and Van Assche [37].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the said geometric restrictions can be lifted for all previous results (many of which are surveyed in [23], and some for other models appear in [13,14,31]; see also [12]).…”
Section: Introductionmentioning
confidence: 95%
“…Notice that we need the C from Lemma 2.17 to be bounded away from π 2 to effectively bound I(E 0 (λ), λ) from below as λ → ∞. [13,Section 2]). Now, if λ is of the form 4π 2 (a 2 − b 2 ) for a, b ∈ N with a > b, then with E = 4a 2 π 2 , it is evident from (23) that λ (E) = (1, 1, 1), which is a point on S 0 that is fixed under the action by f .…”
Section: 4mentioning
confidence: 99%